Towards the very nature of corporate strategy - D. Heil; T. Maxwell; L. Whittaker (South African Journal of Business Management, 2003)
Current approaches to corporate strategy are overwhelmingly based on a metaphorical – and mostly unarticulated – understanding of the essential nature of corporations. In this paper we argue that in order to understand corporate strategy it is critical to understand the very nature of the entity called `corporation'. We then present an understanding of corporations as works; those entities that create and sustain the world in which humans live. In describing the characteristics of works and the way in which they create and sustain a world, we elucidate the very nature of corporate strategy. We conclude by proposing a process to enable leaders of corporations to engage in corporate strategy as creating and sustaining a world.
Keywords: 650